Salvage Therapy in Advanced Adult Soft Tissue Sarcoma: A Systematic Review and Meta‐Analysis of Randomized Trials. (4th December 2017) - Comandone, Alessandro; Petrelli, Fausto; Boglione, Antonella; Barni, Sandro
Abstract: Background: Prognosis for patients with metastatic soft tissue sarcomas (STS) is dismal, with median overall survival (OS) of 8–12 months. The role of second‐line therapy has been inconsistently investigated over the last 20 years. This systematic review and meta‐analysis was performed to assess the efficacy of salvage treatment in pretreated adult type STS, gastrointestinal stromal tumor (GIST) excluded. Material and Methods: PubMed, Web of Science, SCOPUS, EMBASE, CINAHL, and The Cochrane Library were searched for randomized phase II/phase III trials exploring second‐ or beyond therapy lines in pretreated metastatic STS. Two independent investigators extracted data; the quality of eligible studies was resolved by consensus. Hazard ratio (HR) of death and progression (OS and progression‐free survival [PFS]) and odds ratio (OR) for response rate (RR) were pooled in a fixed‐ or random‐effects model according to heterogeneity. Study quality was assessed with the Cochrane's risk of bias tool, and publication bias with funnel plots. Results: Overall, 10 randomized trials were selected. The pooled HR for death was 0.81 (95% confidence interval [CI] 0.73–0.9). Second‐line therapy reduced the risk of progression by 49% (HR = 0.51, 95% CI 0.34–0.76). This translated into an absolute benefit in OS and PFS by 3.3 and 1.6 months, respectively. Finally, RR with new agents or chemotherapy doublets translated from 4.3% to 7.6% (OR = 1.78, 95% CI 1.22–2.50). Conclusion: Better survival is achieved in patients treated with salvage therapies (chemotherapy, as single or multiple agents or targeted biological agents). A 3‐months gain in OS and an almost double RR is observed. Second lines also attained a reduction by 50% the risk of progression. Implications for Practice: There is some evidence that salvage therapies after first‐line failure are able to improve outcome in metastatic soft tissue sarcoma (STS). Trabectedin, gemcitabine‐based therapy, and pazopanib are currently approved drugs used after conventional upfront treatment. This meta‐analysis reviews the benefit of new agents used in randomized trials in comparison with no active treatments or older agents for recurrent/progressed STS. The results show that modern drugs confer a statistically significant 3‐month benefit in terms of overall survival, and an increase in response rate. Despite a limited improvement in outcome, currently approved second‐line therapy should be offered to patients with good performance status. Abstract : This systematic review and meta‐analysis was performed to assess the efficacy of salvage treatment in pretreated adult type soft tissue sarcomas, gastrointestinal stromal tumors excluded. The objective was to compare the main outcome endpoints (progression‐free survival, overall survival, objective response rate) between trials investigating second‐line therapy in soft tissue sarcomas to define the importance and the role of subsequent treatment after first‐line failure.